Differentiated Instruction: Pengembangan Kemampuan Guru untuk Mewujudkan Pembelajaran Berkualitas - Emawati (Bansigom Na Publisher, 2025)
One of the goals of the Sustainable Development Goals (SDGs) program is to realize quality and equitable education. One strategy to ensure the realization of quality education is to implement differentiated instruction. This strategy allows teachers or educators to be creative in teaching students who have different learning abilities. Due to the importance of using differentiated instruction, this study was conducted to obtain information on the implementation of differentiated instruction through library research, where content analysis was used to review articles related to the implementation strategy of differentiated instruction. This study provides information that differentiated instruction is useful in helping students recognize their own abilities, and at the same time provides an understanding for teachers in determining and implementing learning strategies in the classroom.